Prevalence of Iron Deficiency Anaemia in Ischaemic Stroke - Hasan, Md Abdullah Al; Azad, Abul Kalam; Das, Panchanan; Chowdhury, Md Nazmul Hassan (Central Medical College Journal, 2023)
Background: Iron Deficiency Anaemia has been proposed as a risk factor for developing ischemic stroke. In long-term follow-up studies, and it is also known to increase the risk of death. Very little is known about the prevalence of Iron Deficiency Anaemia (IDA) in Bangladeshi stroke patients. We aimed to determine the prevalence of IDA among admitted patients of acute ischemic stroke in a tertiary care hospital in Bangladesh. Materials and methods: In this cross-sectional study, 75 patients with acute ischemic stroke were selected purposively from the Neurology & Medicine Department of Comilla medical college hospital from February 2021 to May 2021. Traditional risk factors for stroke, stroke type and severity at admission were recorded for each patient. Anaemia is defined as haemoglobin <12gm/dl in women & <13gm/dl in men. IDA was defined as serum ferritin level <20 μgm/L in males and <40 μgm/L in females. Results: Mean age was 65.8 (±11.4) years. Sixty percent of patients were male. Hypertension was the most prevalent risk factor present in 73.3% of the cases, followed by diabetes mellitus (49.3%), smoking (28.0%), ischaemic heart disease (25.3%), and dyslipidemia (21.3%). Small vessel strokes were the most common, accounting for 48% of all the patients, followed by large vessels getting affected in 38.7% of the cases. Prevalence IDA was 24%. (95% confidence interval: 14.9%-35.3%). However, the proportion of IDA among patients with severe stroke was 84.6% compared to 11.3% in non-severe strokes (p=0.001). Conclusion: Prevalence of IDA in acute ischemic stroke is significant and it is associated with severe stroke in our hospital. Central Medical College Journal Vol 6 No 1 January 2022 Page: 7-13